Monocytes and neutrophils are associated with clinical features in amyotrophic lateral sclerosis. Issue 1 (14th February 2020) - McGill, Raquel B; Steyn, Frederik J; Ngo, Shyuan T; Thorpe, Kathryn A; Heggie, Susan; Ruitenberg, Marc J; Henderson, Robert D; McCombe, Pamela A; Woodruff, Trent M
Abstract: Immunity has emerged as a key player in neurodegenerative diseases such as amyotrophic lateral sclerosis, with recent studies documenting aberrant immune changes in patients and animal models. A challenging aspect of amyotrophic lateral sclerosis research is the heterogeneous nature of the disease. In this study, we investigate the associations between peripheral blood myeloid cell populations and clinical features characteristic of amyotrophic lateral sclerosis. Peripheral blood leukocytes from 23 healthy controls and 48 patients with amyotrophic lateral sclerosis were analysed to measure myeloid cell alterations. The proportion of monocytes (classical, intermediates and non-classical subpopulations) and neutrophils, as well as the expression of select surface markers, were quantitated using flow cytometry. Given the heterogeneous nature of amyotrophic lateral sclerosis, multivariable linear analyses were performed to investigate associations between patients' myeloid profile and clinical features, such as the Revised Amyotrophic Lateral Sclerosis Functional Rating Scale, bulbar subscore of the Revised Amyotrophic Lateral Sclerosis Functional Rating Scale, change in Revised Amyotrophic Lateral Sclerosis Functional Rating Scale over disease duration and respiratory function. We demonstrate a shift in monocyte subpopulations in patients with amyotrophic lateral sclerosis, with the ratio of classical to non-classical monocytes increased compared with healthy controls. In line with this, patients with greater disease severity, as determined by a lower Revised Amyotrophic Lateral Sclerosis Functional Rating Scale score, had reduced non-classical monocytes. Interestingly, patients with greater bulbar involvement had a reduction in the proportions of classical, intermediate and non-classical monocyte populations. We also revealed several notable associations between myeloid marker expression and clinical features in amyotrophic lateral sclerosis. CD16 expression on neutrophils was increased in patients with greater disease severity and a faster rate of disease progression, whereas HLA-DR expression on all monocyte populations was elevated in patients with greater respiratory impairment. This study demonstrates that patients with amyotrophic lateral sclerosis with distinct clinical features have differential myeloid cell signatures. Identified cell populations and markers may be candidates for targeted mechanistic studies and immunomodulation therapies in amyotrophic lateral sclerosis. Abstract : Monocyte and neutrophil frequencies and their expression markers were associated with bulbar symptoms, disease severity, rate of disease progression and respiratory impairment in patients with amyotrophic lateral sclerosis. Our study reveals that aberrant peripheral immunity is related to amyotrophic lateral sclerosis patient phenotype and supports the need for tailored therapies to modify the immune profile. Graphical Abstract: